Acute kidney injury among adult patients presenting with upper gastrointestinal bleeding in tertiary hospitals in Dodoma, Tanzania - Lioba Joseph; Emmanuel Sindato; Alfred Meremo (Renal Replacement Therapy)
Abstract Introduction The incidence of acute kidney injury (AKI) is highest in low-income countries and among patients with critical illness leading to new onset chronic kidney diseases (CKD), rapid CKD progression, and increased mortality rates. Methodology A prospective observational study was conducted among patients with upper gastrointestinal bleeding (UGIB) attending tertiary hospitals in Dodoma between October 2022 and April 2023. At baseline, patients’ demographic and clinical data were collected; laboratory investigations were done and all were recorded in a questionnaire. Patients were evaluated for AKI using the kidney disease improving global outcomes (KDIGO) criteria at baseline, 48 h, and day 7, and estimated glomerular filtration rate (eGFR) was calculated after 3 months using the chronic kidney disease epidemiology collaboration (CKD-EPI). Data were entered into an Excel spreadsheet and analyzed using SPSS version 27. Multivariate logistic regression analyses were used to identify factors associated with AKI among patients with UGIB. Results A total of 200 patients with UGIB were enrolled into the study with a median age of 62 (IQR 48–69) years; 59.5% were males. The incidence of AKI among adult patients presenting with UGIB was 20% (40/200). For those patients with AKI; the median serum creatinine at 48 h was 142 (98.5–252.5) μmol/L and hemoglobin was 5.75 (5–7) g/dl. Factors associated with AKI among adult patients presenting with UGIB included hepatitis B infection (adjusted odds ratio, AOR 4.9, 95% CI 3.9–9.2, P = 0.001), rebleeding during admission (AOR 4.1, 95% CI 1.0–6.4 P = 0.002), hypertension (AOR 3.9, 95% CI 2.7–6.4, P = 0.007, P = 0.023), using nephrotoxic medicines (AOR 3.2, 95% CI 1.1–8.3, P = 0.041), age ≥ 60 years (AOR = 2.8, 95% CI 1.5–14.7, P = 0.023), diabetes mellitus (AOR 2.1, 95% CI 1.0–3.4 P = 0.002), and variceal bleeding (AOR 2.0, 95% CI 1.1–10.7, P = 0.043). After 3 months of follow-up, of the patients with AKI, 32.5% (13/40) developed CKD and 17.5% (7/40) died. Conclusion The incidence of AKI and its associated mortality is high among adult patients presenting with UGIB in our settings. More than one-third of the patients who were found with AKI progressed to CKD.